Langzeit-Trends bei kommunalen Unternehmen: mehr und komplexere Auslagerungen - Christian Raffer; Maike Rackwitz (Wirtschaftsdienst, 2024)
There is a trend towards the creation of additional public companies at the municipal level. An analysis of 34 cities in the state of North Rhine-Westphalia examines what explains this development. What influence does the different transparency of municipalities have? What effects do the character traits of mayors have? And what influence do debt relief programs have?
Keywords: R53; H72; H82; 330